Surgery in recurrent brain glioma, does it improve clinical outcome? - Ahmed Elshanawany; Mohamad Sayed Waer; Ahmad Algheriany; Farrag Mohammad Farrag (Egyptian Journal of Neurosurgery)
Abstract Introduction Gliomas account for 24% of all primary brain and CNS tumors. Histologically, gliomas were categorized into subtypes and grades (I through IV). Low-grade gliomas are grade I and grade II, while high-grade gliomas are grade III and grade IV. The gold standard for treatment of high-grade glioma is the most extensive safe surgical resection followed by radiotherapy combined with chemotherapy. However, recurrence of glioma is inevitable. Management of recurrent cases is still controversy. Aim of the work The purpose of this research was to examine the efficacy of reoperation for cases of recurrent glioma in improving patients’ outcome. Methods This study included 25 patients with recurrent glioma admitted and operated upon in neurosurgical department in Assiut University hospitals through 1 year from 1/11/2020 to 30/10/2021. Results There were 17 male (68%) and 8 female (32%), their age incidence ranged from 25 to 74 years with a mean age of 49.09, gross total resection of recurrent cases could be done in 14 (56%) patients, subtotal resection in 6 (24%) and partial in 5 (20%), all of recurrence were found at the same site almost the same of primary tumor except that two cases were radionecrosis and one patient revealed aggressive transformation from anaplastic astrocytoma to GBM by the end of the study period, and 17 (68%) patients alive and 8 (32%) died. Conclusion Surgical management of recurrent gliomas in selected patients is generally associated with improved functional performance and prolonged survival. Patients’ Karnofsky score at recurrence is an important prognostic factor for both low-grade glioma and high-grade glioma.